Systematic Review of the Negative Impact of Early Childhood Education Learning Digitalization on Early Childhood Development - Fauziddin, Mohammad; Ningrum, Mallevi Agustin; Adamcova, Petra; Utari, Aulia Rahmi (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study aims to critically analyze the negative impacts of digitalization of Early Childhood Education (ECE) learning on early childhood development. Systematic Literature Review (SLR) was chosen in this writing by identifying, analyzing, and synthesizing relevant academic literature study results from 2015 to 2025 from various scientific databases. The total number of articles reviewed was 20 in Indonesian and English. The analysis results show that excessive use of digital media can have negative impacts on children's physical, cognitive, social, and emotional development. These include increased risk of obesity, language development delays, decreased social skills, and the emergence of anxiety and depression. The research also found that the type and intensity of digital media use as well as parental involvement play important roles in strengthening or reducing these impacts. The involvement of parents and educators becomes an important point in wisely regulating digital media use and setting time limits for its use. This study provides theoretical and practical foundations for formulating ECE education policies that are adaptive to the digital era while considering holistic aspects of child development.